Peperangan Generasi Digital Natives Melawan Digital Hoax Melalui Kompetisi Kreatif - Astuti, Yanti Dwi (Universitas Negeri Yogyakarta, 2017)
The phenomenon of hoax and hate speech dissemination that occurs in the digital worldhas brought anxiety and concern in the community. Many of the hoax informationdistributed by Social Media and Instant Messaging tend to be SARA, provocative andbombastic. Ironically, not a few people who without thinking directly spread informationand even reproduce the information without thinking about the impact caused after.Digital media is currently dominated by teenagers born in the millennium era and is a